2020
DOI: 10.1186/s13023-020-01532-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of a patient-reported outcome questionnaire for aplastic anemia and paroxysmal nocturnal hemoglobinuria (PRO-AA/PNH)

Abstract: Background The introduction of new therapy modalities has significantly improved the outcome of aplastic anemia (AA) and paroxysmal nocturnal hemoglobinuria (PNH) patients. However, relatively little is known about the exact disease burden of AA/PNH since standardized assessments of symptoms including health-related quality of life (HRQoL) are frequently missing or inadequately designed for this rare patient group. We aimed to develop AA/PNH-specific questionnaires for self-reporting of symptom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The EORTC QLQ-C30 and the FACIT-F were originally developed for use in evaluations of HRQoL among people with cancer, with their validity extended to people with PNH. Other PRO questionnaires are available for patients with PNH that encompass additional aspects of the disease [ 37 , 38 ]. Potential collection mode-related and non-response biases may have been introduced.…”
Section: Discussionmentioning
confidence: 99%
“…The EORTC QLQ-C30 and the FACIT-F were originally developed for use in evaluations of HRQoL among people with cancer, with their validity extended to people with PNH. Other PRO questionnaires are available for patients with PNH that encompass additional aspects of the disease [ 37 , 38 ]. Potential collection mode-related and non-response biases may have been introduced.…”
Section: Discussionmentioning
confidence: 99%
“…53 Differences in PRO prioritization between patients and physicians have also been observed in other comparable studies. Weisshaar et al 54 found substantial variations in ratings between patients and physicians, in a study for PRO selection in aplastic anemia and paroxysmal nocturnal hemoglobinuria. Issues related to QoL (e.g., mood disturbances, fatigue and impaired activities of daily living) were rated higher by patients than by hematologist experts, who prioritized physical constraints (e.g., bleeding, fever, hemoglobinuria).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the patient-reported outcome questionnaire for aplastic anemia and paroxysmal nocturnal hemoglobinuria (PRO-AA/PNH) was developed [23]. However, upon comparison of the measures, only some of the 10 PNH-SQ items are also measured in the PRO AA/PNH (e.g., fatigue, shortness of breath, difficulty concentrating, and dysphagia).…”
Section: Discussionmentioning
confidence: 99%